2017
DOI: 10.4103/jispcd.jispcd_275_16
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial efficacy of tender coconut water (Cocos nucifera L) on Streptococcus mutans: An in-vitro study

Abstract: Objective:The antibacterial property of coconut, the presence of lauric acid, and the ability to extract antimicrobial peptides Cn-AMP (1, 2, and 3) from tender coconut water has drawn attention on its effectiveness in normal consumption. An in-vitro experimental study was conducted to evaluate the antimicrobial efficacy of tender coconut water in its natural state on Streptococcus mutans.Materials and Methods:Fresh tender coconut water and pasteurized tender coconut water were taken as test samples, dimethyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 8 publications
0
13
1
Order By: Relevance
“…Infections in animals are accompanied by high serum total protein, elevated globulin and low albumin levels resulting from enhanced antibody secretion in response to infection (Orhue et al,2005;Wamboi et al, 2020). Coconut water supplementation seemingly reduced susceptibility of birds in groups B and C to infection probably as a result of its antimicrobial properties (Rajan et al, 2016;Rukmini et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infections in animals are accompanied by high serum total protein, elevated globulin and low albumin levels resulting from enhanced antibody secretion in response to infection (Orhue et al,2005;Wamboi et al, 2020). Coconut water supplementation seemingly reduced susceptibility of birds in groups B and C to infection probably as a result of its antimicrobial properties (Rajan et al, 2016;Rukmini et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It contains chemical constituents such as vitamins, amino acids, selenium, cytokinins (kinetin), minerals (Bhagya et al, 2010) and lauric acid. Antimicrobial properties of coconut water have been shown by different studies (Rajan et al, 2016;Rukmini et al, 2017). Kinetin was reported to have pro-proliferative effect on cells (Lee et al, 2006) and immune cells (Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Anthelmintic activity of coconut water has not been studied. Antibacterial: an in vitro study on Streptococcus mutans showed no zone of inhibition using both fresh and pasteurized coconut water (Rukmini et al, 2017). Gastroprotective: coconut water (2 ml/d PO for 40 days) reduced indomethacin-induced formation of gastric ulcers in rats by 39% (Nneli and Woyike, 2008).…”
Section: Possibly Safe and Effective D32mentioning
confidence: 99%
“…Coconut water has various health benefits, namely it prevents oxidative damage due to its antioxidant content, helps rehydration and supports physical performance, as well as prevents and lowers a high blood pressure [1][2][3]5]. Coconut water also has antiobesity and antiinflammatory, antibacterial, antitumour, and antidiabetic effects [5][6][7][8]. Young coconut water can reduce insulin levels and plasma glucose in rats fed on fructose [4].…”
Section: Introductionmentioning
confidence: 99%